Estimating population size of Pacific harbor seals (Phoca vitulina richardsi) at Children's Pool Beach in La Jolla, California, using photo-identification - Linder, Traci A. (eScholarship, University of California, 2011)
Children's Pool Beach in La Jolla, CA is a Pacific harbor seal (Phoca vitulina richardsi) rookery at the center of a large legal controversy. Due to the heated contention surrounding this rookery, very few scientific studies have been done on the population of harbor seals that use this haul-out site. Maximum daily haul-out counts rarely exceed 200, and management decisions have been framed around the assumption of a largely resident population of no more than approximately 250 seals. In this study I used photo- identification and mark-recapture methods to estimate the total population of Pacific harbor seals that used Children's Pool Beach as a haul-out site during January - October 2008. I photographed the ventral surfaces of adult harbor seals at Children's Pool Beach, and then entered each good to high quality photograph into an interactive computer-assisted photograph-matching system for individual identification. Each individual identification was confirmed by both a trained volunteer and myself, resulting in a 4% visual matching error rate. After analysis concluded, 480 unique adult harbor seals were individually identified after applying the 4% visual matching error rate. Abundance estimation was calculated using the Chapman-Petersen capture-recapture model. My calculations yielded a population estimate of 596 individuals during January - October 2008, which is two to three times larger than previously believed. These findings suggest a population that is at least partially open with considerable coastal movement, suggesting that Children's Pool Beach is potentially part of a regional network of interconnected haul-out site